Hubungan Pengetahuan Lansia Tentang Dash dengan Perilaku Dash pada Lansia Hipertensi di Posyandu Lansia Desa Campurejo Kecamatan Bojonegoro Kabupaten Bojonegoro - Saskiyanti Ari Andini; Moh Roni Al Faqih; Sahrir Ramadhan; Ahmad Rizal Bakhtiar (Pusat riset dan Inovasi Nasional, 2025)
Hypertension is a prevalent health problem among the elderly and may lead to severe complications if not properly managed. One of the effective non-pharmacological approaches is the DASH diet (Dietary Approaches to Stop Hypertension). This study aims to examine the relationship between elderly knowledge about the DASH diet and their behavior in applying it, particularly among hypertensive elderly at the Posyandu Lansia in Campurejo Village, Bojonegoro District. This correlational study applied a cross-sectional design and involved a total sampling of 36 elderly respondents with hypertension. The data were collected using a closed-ended questionnaire that had been validated and tested for reliability. Data were analyzed using the Spearman Rho test. The findings revealed that most respondents had moderate levels of knowledge and behavior related to the DASH diet. The statistical test indicated a significant relationship between knowledge and DASH diet behavior (ρ = 0.000; p < 0.05). These results suggest that the higher the knowledge of the elderly about the DASH diet, the better their implementation behavior. Effective health education is essential to improve compliance among the elderly in managing hypertension through the DASH diet.